Use of Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes (hiPSC‐CMs) to Monitor Compound Effects on Cardiac Myocyte Signaling Pathways. Issue 3 (1st September 2015) - Guo, Liang; Eldridge, Sandy; Furniss, Mike; Mussio, Jodie; Davis, Myrtle
Abstract : There is a need to develop mechanism‐based assays to better inform risk of cardiotoxicity. Human induced pluripotent stem cell–derived cardiomyocytes (hiPSC‐CMs) are rapidly gaining acceptance as a biologically relevant in vitro model for use in drug discovery and cardiotoxicity screens. Utilization of hiPSC‐CMs for mechanistic investigations would benefit from confirmation of the expression and activity of cellular pathways that are known to regulate cardiac myocyte viability and function. This unit describes an approach to demonstrate the presence and function of signaling pathways in hiPSC‐CMs and the effects of treatments on these pathways. We present a workflow that employs protocols to demonstrate protein expression and functional integrity of signaling pathway(s) of interest and to characterize biological consequences of signaling modulation. These protocols utilize a unique combination of structural, functional, and biochemical endpoints to interrogate compound effects on cardiomyocytes. © 2015 by John Wiley & Sons, Inc.